ANALISIS HUBUNGAN KESEHATAN KERJA DENGAN KEJADIAN KECELAKAAN KERJA PADA KARYAWAN LAPANGAN BAGIAN PEMANENAN KAYU DI PT. CITRA SUMBER SEJAHTERA SEJATI - Dyah Endah Astuti Nasution; Aras Mulyadi; Yulis Hamidy (Jurnal Ilmu Lingkungan, 2015)
Development in industial makes many new industries or companies grow in Indonesia. It candecrease the number of jobless in Indonesia, but there are more work accidents as a negativeeffect of it. Employees are one of the important things in an industry or company because almostall of the activities need their help, so an industry or company should give more attentions to thework healthy condition in a work place to guaranty the employees’ occupational health andsafety. In the fact, there are still many industries or companies especially in Indonesia haven’tgiven more attention to the work helathy in their companies. The effect of this condition is thereare still many work accident cases in Indonesia. It is very and should found out the best solutionsas soon as possible. This research is aim to know and analyse the correlation betweenoccupational health and work accident of field employess in harvesting part at PT.CSSS. Thisresearch is descriptive analitic research with cross sectional study desain. Population of thisresearch is all of the employess in harvesting at PT.CSSS, they are 90 persons. This research usetotal sampling as sampling technique, so there are 90 persons also as sample of this research.Data analysis which is used in this research is bivariat with chi square test and relative risk/ riskratio (RR). Result of this research show that 5 of 6 sub variables of occupational health havecorrelation with frequences of work accident; they are age ( count = 6,555, RR= 2,39),knowledge level ( count = 25,620, RR= 2,76), work stress level ( count = 26,338, RR=3,03), work motivation level ( count = 29,2017, RR= 5,14), and noise level ( count = 28,88,RR= 2,84). But, sub variable working time ( count = 6, 428, RR = 1, 17) doesn’t havecorrelation with work accident frequence. Then, all of sub variables of occupational health havecorrelation with the kinds of work accidents, they are age ( count = 4,566, RR= 3,14), workingtime ( count = 19,116, RR= 2,32), knowledge lnevel ( count = 15,977, RR= 2,38), workingstress level ( count = 34,417, RR= 4,73), working motivation level ( count = 57,809, RR=3,26), and noise level ( count = 35,544, RR= 6,4)